How Application Ease Affects Buying Interest: ShopeeFood Study among University Students - Setiyaningsih, Mitta; Saptariana, Saptariana; Suryatna, Bambang Sugeng; Rachmawati, Rina (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
Buying interest is impacted by multiple factors, among which perceived ease of use plays a crucial role. This study aims to examine how the perceived ease of using applications affects Universitas Negeri Semarang students' interest in buying food products through ShopeeFood and the extent of its influence. Data collection involved distributing questionnaires to 100 respondents based on specific criteria. The analysis methods utilized comprised descriptive percentage testing and regression analysis. Findings from the descriptive percentage test indicated that the majority of respondents found ShopeeFood easy to use, and their interest in buying through the platform was notably high. Regression analysis revealed a positive and significant relationship between perceived ease of use and buying interest, represented by the equation = 11.702 + 0.402X. This signifies that perceived ease of use has a meaningful impact on buying interest. The R2 value of 40.4% illustrates that perceived ease of use influences 40.4% of the interest in online purchases via ShopeeFood.